Pendugaan Parameter Genetik Pertumbuhan Dan Produksi Tanaman Cabai Katokkon Capsicum chinense Jacq - Febrianty, Ine; Muhibuddin, Andi; Maulana, Zulkifli (PALLANGGA: Journal of Agriculture Science and Research, 2024)
Katokkon chili or commonly known as "lada katokkon" is a typical Tana Toraja chili that has a shape like peppers but has a smaller size and a distinctive aroma, as well as a spicy taste that is higher than other types of chili. The research was carried out in the form of experiments and arranged according to a Randomized Block Design (RBD) with 4 treatments 3 replications so as to obtain 15 experimental units, this study without using. The purpose of this study was to determine the estimation of genetic parameters of several growth and production characters of katokkon chili plants. This research was conducted at BTP Tamalanrea, Tamalanrea District, Makassar City, South Sulawesi and at the Green House of the Integrated Farming System Educational Garden, located at Raya poros Sapayya street, Bontoramba Village, Palangga District, Gowa Regency.  Based on the results of the study, it can be concluded that the heritability value of plant height, leaf number, stem diameter, flowering age, fruit diameter, and fruit weight per plant has a high heritability value. Medium heritability is found in the character of fruit length and harvest age. Low heritability value is found in the character of fruit stalk length. Cabai katokkon atau biasa di kenal dengan “lada katokkon” merupakan cabai khas Tana Toraja yang memiliki bentuk seperti paprika tetapi memiliki ukuran yang lebih kecil dan aroma yang khas, serta rasa pedasnya yang lebih tinggi dari jenis cabai lainnya. Penelitian dilaksanakan dalam bentuk percobaan dan disusun menurut Rancangan Acak Kelompok (RAK) dengan 4 perlakuan 3 ulangan sehingga diperoleh 15 unit percobaan. Tujuan penelitian ini untuk mengetahui pendugaan parameter genetik dari beberapa karakter pertumbuhan dan produksi tanaman cabai katokkon. Penelitian ini dilaksanakan di BTP Tamalanrea, Kecamatan Tamalanrea, Kota Makassar, Sulawesi Selatan dan di Green House kebun pendidikan Integrated Farming System di Jalan Raya poros Sapayya, Desa Bontoramba, Kecamatan Palangga, Kabupaten Gowa. Berdasarkan hasil penelitian dapat disimpulkan bahwa yang memiliki nilai heritabilitas tinggi tanaman, jumlah daun, diameter batang, umur berbunga, diameter buah, dan berat buah per tanaman mempunyai nilai heritabilitas yang tinggi. Untuk heritabilitas sedang terdapat pada karakter panjang buah dan umur panen. Nilai heritabilitas rendah terdapat pada karakter panjang tangkai buah.